An Action Research Case Study on Water Awareness Program in The Rural Schools in Goa - Dr, Padhmannabhan (Journal of Contemporary Research in Management (JCRM), 2019)
According to a research conducted by MIT, it is estimated that over 50% 1 of the global population will struggle to fetch adequate water to meet their basic needs by the year 2050 2 . Currently, around 663 million population are still without adequate drinking water and sooner 3.3 billion people will face water crisis 3 . Studies reveal that vulnerable group of population, mostly children, would suffer due to diseases related with poor water supply and associated sanitation and hygiene problems. That data also reveals noted that nearly 1000 children each day would die due to water and sanitation related diseases such as diarrhoea. The world population reliance on the drinking water resource has drastically increased from 76% to 91% 4 . Clean water is vital to meet basic survival needs of human being. An inadequacy or a scarcity will lead to severe health related issues, starvation, and a major global crisis. Variety of factors contributes to inadequate supply and scarcity of water. In the past years particularly, India faced drought effecting the Agriculture GDP by bringing it down to 0.5 % between 2015-16. Severe drought condition in Maharashtra has forced the government to act by sending train carrying water to some regions in that state. Out of 678, about 250 5 districts faced drought and near to drought condition in India. In India or anywhere in the world, water dominates primary role in policy related to economy and environment. UN has taken major steps concerned to water security by creating a Sustainable Development Goal focusing on this issue. It is crucial to note that other SDG global goals (annexure – I) on poverty, affordable and clean energy, decent work and economic growth, good health and well-being, hunger, sustainable consumption and production, climate change, life below water, and life on land, are strongly connected with this SDG -6 on clean water and sanitation (annexure – II).